2021
DOI: 10.3892/etm.2021.9671
|View full text |Cite
|
Sign up to set email alerts
|

Experimental models in peritoneal dialysis (Review)

Abstract: Peritoneal dialysis (PD) is one of the most commonly used dialysis methods and plays an important role in maintaining the quality of life of patients with end-stage renal disease. However, long-term PD treatment is associated with adverse effects on the structure and function of peritoneal tissue, which may lead to peritoneal ultrafiltration failure, resulting in dialysis failure and eventually PD withdrawal. In order to prevent the occurrence of these effects, the important issues that need to be tackled are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Previous experimental studies of PD have either been on rats with normal kidney function, uremic rats after nephrectomy or uremia induced by drugs (adenine or adriamycin). 11 In this study, to avoid surgical trauma, dialysis-dependent kidney disease was introduced by the nephrotoxin orellanine. Orellanine is a compound found in the Cortinarius family of mushrooms that specifically targets the tubular epithelium, where it causes irreversible damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experimental studies of PD have either been on rats with normal kidney function, uremic rats after nephrectomy or uremia induced by drugs (adenine or adriamycin). 11 In this study, to avoid surgical trauma, dialysis-dependent kidney disease was introduced by the nephrotoxin orellanine. Orellanine is a compound found in the Cortinarius family of mushrooms that specifically targets the tubular epithelium, where it causes irreversible damage.…”
Section: Discussionmentioning
confidence: 99%
“…The first approach uses only intraperitoneal (ip) injection of PD fluid, without draining the fluid, and the second involves implanting a peritoneal catheter enabling drainage of the PD fluid. 11 The most common method for achieving a state similar to that of clinical uremia in these PD rat models is 5/6 nephrectomy, 6 , 12 16 which requires surgical trauma. However, these rats do not develop clinically relevant dialysis-dependent uremia.…”
Section: Introductionmentioning
confidence: 99%
“…After day 0 (before 5/6 nephrectomy) and day 21, serum urea and creatinine levels were measured to confirm the successful modeling of uremia. The mice were then exposed to 2 ml of standard PDF (4.25% g/dL dextrose) daily for a period of 6 weeks in all PD groups ( Ferrantelli et al, 2016 ; Yang et al, 2021 ). Mice in the PD + AS IV group and the 5/6 Nx + PDF + AS IV group were intragastrically treated with AS IV (10 mg/kg/d, purity ≥98%, Adamas, Shanghai, China) ( Jiang et al, 2017 ; Gao et al, 2020 ) for 6 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…), [81,82] with each model having its own set of advantages and disadvantages. [83] Currently, rat models are considered a suitable animal peritoneal dialysis model due to their low cost, ease of performing a surgical operation on them, large enough for our implant, and are a relatively stable model. [81,83,84] In animal models, peritonitis can be induced by injecting pathogenic microorganisms (such as Staphylococcus aureus, Staphylococcus epidermis, Pseudomonas aeruginosa) into the peritoneal cavity.…”
Section: Animal Studymentioning
confidence: 99%
“…[83] Currently, rat models are considered a suitable animal peritoneal dialysis model due to their low cost, ease of performing a surgical operation on them, large enough for our implant, and are a relatively stable model. [81,83,84] In animal models, peritonitis can be induced by injecting pathogenic microorganisms (such as Staphylococcus aureus, Staphylococcus epidermis, Pseudomonas aeruginosa) into the peritoneal cavity. It has been shown that rodents have a strong peritoneal defense system, therefore they require a large inoculum to develop disease (LD50 of 5 × 10 8 CFU and LD90 of 6×10 9 CFU for S. aureus Strain Newman for mouse).…”
Section: Animal Studymentioning
confidence: 99%